2016
DOI: 10.1093/ndt/gfw064
|View full text |Cite
|
Sign up to set email alerts
|

Renal effects of novel antiretroviral drugs

Abstract: Chronic kidney disease (CKD) is a critical comorbidity for patients living with HIV, with an estimated prevalence between 2.4 and 17%. Such patients are increasingly affected by diseases associated with ageing, including cardiovascular disease and CKD, and the prevalence of risk factors such as smoking and dyslipidaemia is increased in this population. Proteinuria is also now recognized as a common finding in individuals living with HIV. While combination antiretroviral (ARV) treatments reduce CKD in the HIV-i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
52
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(57 citation statements)
references
References 45 publications
2
52
0
3
Order By: Relevance
“…Interestingly, in our study, we found lower baseline eGFR, nadir CD4 counts, uncontrolled viremia, and current PI/r use associated with incident CKD. Although we did not have adequate power to determine which PI/r was associated with CKD, previous analyses have indicated that ATV causes nephrolithiasis and is associated with development of interstitial nephritis, switching from ATV/r or LPV/r to DRV/r is associated with improvement in kidney function, and use of a concomitant PI/r with TDF amplifies the renal toxicity of the later due to inhibition of Multi‐resistant Protein 4 (MRP‐4) efflux channels in the proximal tubular cells by ritonavir leading to TDF accumulation in the cells …”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, in our study, we found lower baseline eGFR, nadir CD4 counts, uncontrolled viremia, and current PI/r use associated with incident CKD. Although we did not have adequate power to determine which PI/r was associated with CKD, previous analyses have indicated that ATV causes nephrolithiasis and is associated with development of interstitial nephritis, switching from ATV/r or LPV/r to DRV/r is associated with improvement in kidney function, and use of a concomitant PI/r with TDF amplifies the renal toxicity of the later due to inhibition of Multi‐resistant Protein 4 (MRP‐4) efflux channels in the proximal tubular cells by ritonavir leading to TDF accumulation in the cells …”
Section: Discussionmentioning
confidence: 99%
“…With respect to CKD screening, in contrast to routine lab-monitoring, a targeted approach based on a CKD risk score could be adapted to African populations and applied during treatment initiation [ 29 ]. Additionally, HIV programmes should consider the use of newer ARTs with less nephrotoxic effects such as integrase inhibitors and Tenofovir alafenamide (TAF), in particular if continuous renal monitoring is not feasible [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, comorbidities and ART may lead to renal injury [ 2 ]. The incidence of chronic kidney disease (CKD) in patients living with HIV (PLWH) ranges from 2 to 17% although the extent of renal injury depends on individual patient factors [ 3 ].…”
Section: Introductionmentioning
confidence: 99%